2019
DOI: 10.1080/09602011.2019.1611606
|View full text |Cite
|
Sign up to set email alerts
|

The development of a manual-based digital memory notebook intervention with case study illustrations

Abstract: There is currently a need to identify feasible and effective interventions to help older individuals suffering from memory loss maintain functional independence and quality of life. To improve upon paper and pencil memory notebook interventions, the Digital Memory Notebook (DMN) application (app) was developed iteratively with persons with cognitive impairment. In this paper we detail a manual-based intervention for training use of the DMN app. A series of three case studies are described to illustrate the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Compensation, as measured by self- and informant-report, has been found to increase at early stages of age-related cognitive disorders (Schmitter-Edgecombe, Parsey, & Lamb, 2014) and then decrease with advanced impairment (Schmitter-Edgecombe et al, 2014; Tomaszewski Farias et al, 2018). It has also been demonstrated that individuals with mild forms of cognitive impairment can learn to use strategies to compensate for cognitive impairment suggesting a possible point of intervention (Chudoba, Church, Dahmen, Brown, & Schmitter-Edgecombe, 2019; Schmitter-Edgecombe, Howard, Pavawalla, Howell, & Rueda, 2008; Schmitter-Edgecombe & Dyck, 2014; Troyer, Murphy, Anderson, Moscovitch, & Craik, 2008). Collectively, this research may suggest that people naturally adapt to changes in cognitive ability and they have the capacity to learn and apply new strategies to improve overall daily functioning.…”
mentioning
confidence: 99%
“…Compensation, as measured by self- and informant-report, has been found to increase at early stages of age-related cognitive disorders (Schmitter-Edgecombe, Parsey, & Lamb, 2014) and then decrease with advanced impairment (Schmitter-Edgecombe et al, 2014; Tomaszewski Farias et al, 2018). It has also been demonstrated that individuals with mild forms of cognitive impairment can learn to use strategies to compensate for cognitive impairment suggesting a possible point of intervention (Chudoba, Church, Dahmen, Brown, & Schmitter-Edgecombe, 2019; Schmitter-Edgecombe, Howard, Pavawalla, Howell, & Rueda, 2008; Schmitter-Edgecombe & Dyck, 2014; Troyer, Murphy, Anderson, Moscovitch, & Craik, 2008). Collectively, this research may suggest that people naturally adapt to changes in cognitive ability and they have the capacity to learn and apply new strategies to improve overall daily functioning.…”
mentioning
confidence: 99%
“…Commission errors, which were more prominent in the PDD group, were not corrected after presentation of the goal cues (Giovannetti et al, 2015). Future studies should consider participants’ functional deficit profiles when evaluating the efficacy and effectiveness of interventions and exploit assistive technologies to reduce omissions by promoting the activation of weak task goals through the delivery of cues and prompts (Chudoba et al, 2020; Das et al, 2012; Seelye et al, 2013, 2012). Assistive technologies also should be developed specifically to reduce commissions by facilitating executive control over goal activations by increasing attention between subgoals and by explicitly instructing individuals to identify target objects and remove distractor objects before performing an everyday task (Bettcher et al, 2011; Morady & Humphreys, 2011).…”
Section: Future Directionsmentioning
confidence: 99%
“…delivery of cues and prompts (Chudoba et al, 2020;Das et al, 2012;Seelye et al, 2013Seelye et al, , 2012. Assistive technologies also should be developed specifically to reduce commissions by facilitating executive control over goal activations by increasing attention between subgoals and by explicitly instructing individuals to identify target objects and remove distractor objects before performing an everyday task (Bettcher et al, 2011;Morady & Humphreys, 2011).…”
Section: Clinical Practicementioning
confidence: 99%
“…For instance, people often report using a calendar to support everyday memory but do not have a consistent habit of checking that calendar. Training people to create a new habit of consistent calendar referral can mitigate forgetting appointments ( Chudoba et al, 2019 ).…”
Section: Background and Objectivesmentioning
confidence: 99%